Contención del movimiento: prensa y asociaciones cívicas en Zacatecas, 1824-1833 - Ríos Zúñiga, Rosalina (El Colegio de México, A.C., 2002)
This essay explores the  development of press and civic associations in Zacatecas during the years 1821 to 1845. Both vehicles had a strong link and helped to emerge local public spaces. After an open and dynamic beginning, in which they helped to expand republican political culture, and also created expectations among  lower classes to  citizenship, they  were closed down  by elites.  This  closing happened  principally as an  elite reaction against the popular revolt that occurred in Sombrerete at the beginning of 1829, and it lasted until 1845.